Holland Tanszék alapításának kísérlete a két világháború között - Bozzay, Réka (Gerundium, 2016)
An Attempt to Establish a Department of Dutch Between the Two World Wars. On 20th June, 1921, Ms. Catharina Kuyper, daughter of the former prime minister of the Netherlands, visited Debrecen. This occasion brought the rector of the Hungarian Royal István Tisza University of Debrecen to write her a letter and ask her to convince the Dutch government of the importance of a Department of Dutch Literature and Culture at this university. Kuyper agreed with this wish and promised the board of the university her mediation to raise money for the new department. The managers of the university found a qualified person, dr. Zsigmond Nagy, for the leadership of the Dutch Studies. They received only goodwill support from the Hungarian government but no money. Nagy died in the spring of 1922 and the Dutch government refused to help establish a new Dutch department because of the hard financial situation of the Netherlands.